The Influence of Promotion, Financial Literacy, and Income on Interest Small and Medium Enterprise (SME) Applying for Financing to Sharia Microfinance Institutions (LKMS) - Ramadhani, Putri; Hafizh, Muhammad; Falahuddin, Falahuddin; Damanhur, Damanhur (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to determine the influence of promotion, financial literacy and income on interest in small and medium enterprises (SME) applying for financing at sharia microfinance institutions (LKMS) in Lhokseumawe city. The sampling technique uses Random sampling. The total sample was 96 people in the city of Lhokseumawe. Research data was analyzed using PLS-SEM (Partial Least Square – Structural Equation Modeling) with Smart PLS 3 Software. The research results showed that the Promotion variable did not have a positive influence on Small and Medium Enterprise (SME) interest in applying for financing at Sharia Microfinance Institutions (LKMS). Meanwhile, the financial literacy and income variables have a significant positive influence.